Neutron Beta Decay and Exact Conservation of Charged Weak Hadronic Vector Current in the Standard Model - Derar Altarawneh; Roman Höllwieser; Markus Wellenzohn (Universe)
We investigate the reliability of the hypothesis of exact conservation of the charged weak hadronic vector current in neutron <semantics>β−</semantics>-decay with a polarized neutron and an unpolarized proton and electron. We calculate the contributions of the phenomenological term responsible for Exact Conservation of the charged weak hadronic Vector Current (or the ECVC effect) in neutron <semantics>β−</semantics>-decay, even for different masses of the neutron and proton, to the correlation coefficients, together with a complete set of contributions of scalar and tensor interactions beyond the Standard Model (SM). We argue that if the total contributions of scalar and tensor interactions beyond the SM fail to reconcile the experimental data on the correlation coefficients with the contributions of the ECVC effect, one may conclude that the charged weak hadronic vector current is not conserved in the hadronic transitions of weak processes with different masses of incoming and outgoing hadrons.